2015
DOI: 10.1111/pce.12492
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparative analysis of microRNAs in barnyardgrass (Echinochloa crus‐galli) in response to rice allelopathy

Abstract: Rice allelopathy is a hot topic in the field of allelopathy, and behaviour of donor allelopathic rice has been well documented. However, few study addresses response of receiver barnyardgrass (BYG). We found that expression of miRNAs relevant to plant hormone signal transduction, nucleotide excision repair and the peroxisome proliferator-activated receptor and p53 signalling pathways was enhanced in BYG co-cultured with the allelopathic rice cultivar PI312777, the expression levels of these miRNAs in BYG plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…Cyanamide alters the expression of the expansin genes, LeEXPA9 and LeEXPA18 , which are responsible for cell wall remodeling after cytokinesis, thereby inhibiting the formation of tomato root ( Soltys et al, 2012 ). In a recent study, Fang et al (2015) found that the expression levels of miRNAs relevant to plant hormone signal transduction, p53 signaling pathways, nucleotide excision repair and the peroxisome proliferator-activated receptor were enhanced in barnyard grass co-cultured with allelopathic rice or treated with rice-produced phenolic acids. Kato-Noguchi et al (2013) reported that the rice allelochemicals momilactone A and B might inhibit the germination of Arabidopsis seeds by inhibiting the degradation process of the storage proteins cruciferin and cruciferina.…”
Section: Influence On Protein and Nucleic Acid Synthesis And Metabolimentioning
confidence: 99%
“…Cyanamide alters the expression of the expansin genes, LeEXPA9 and LeEXPA18 , which are responsible for cell wall remodeling after cytokinesis, thereby inhibiting the formation of tomato root ( Soltys et al, 2012 ). In a recent study, Fang et al (2015) found that the expression levels of miRNAs relevant to plant hormone signal transduction, p53 signaling pathways, nucleotide excision repair and the peroxisome proliferator-activated receptor were enhanced in barnyard grass co-cultured with allelopathic rice or treated with rice-produced phenolic acids. Kato-Noguchi et al (2013) reported that the rice allelochemicals momilactone A and B might inhibit the germination of Arabidopsis seeds by inhibiting the degradation process of the storage proteins cruciferin and cruciferina.…”
Section: Influence On Protein and Nucleic Acid Synthesis And Metabolimentioning
confidence: 99%
“…crus-galli which has not been reported before. This phenomenon needs to be further studied to reduce the napropamide dosage in order to promote sustainable agriculture practice (Fang et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our previous research comparatively studied the composition difference of microbial communities in the rhizosphere soil of allelopathic and non-allelopathic rice accessions and found 31 unique microbial genera in the rhizosphere soil of allelopathic rice PI312777, seven of which belongs to myxobacteria at the rice seedling stage (3-7 leaf stage) (Xiong et al, 2012). Fang et al (2015) documented that the inhibitory effect of allelopathic rice accessions on target barnyard grass under field conditions might be related to miRNA expression, which is associated with nucleotide excision repair, auxin signal and its transduction pathway in target barnyard grass, thereby reducing its ability to repair DNA damage, subsequently resulting in blocked synthesis of auxin and ultimately repressing the growth of barnyard grass. However, what is involved in the rhizosphere biological process still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further investigate the correlation between rice OsPAL2-1 gene expression abundance and myxobacteria populations in its rhizosphere the possible link between them needs to be explored. In this study, allelopathic rice PI312777 (PI), its genetically modified OsPAL2-1 repression (PR) or overexpression (PO) lines, and non-allelopathic rice Lemont (Le) were taken as research materials; these genetically modified lines were developed in our previous studies (Fang et al, 2015;Li et al, 2020). The population number of Myxococcus sp.…”
Section: Introductionmentioning
confidence: 99%